PRACTICE ORIENTED HEAT SOURCE MODEL CALIBRATION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The modelling of the thermal process is used as a tool in determination of the properties of the materials, subject to welding. One of the most important steps in the modelling is the calibration of the heat source model. This is a necessary condition for a given model to be used to solve practical problems. The standard practice in this regard is to calibrate the model by the shape of the melted zone or by the temperature cycles at set points. In the present work, the heat source model calibration based on the maximum temperatures measured at several surface points, at different distances from the seam line, is considered. The temperature cycles in the welded joint and the penetration depth were assumed by the model, calibrated in such non-destructive way. The calculated temperature cycles were compared with records of the temperature during welding. The actual penetration depth was measured by metallographic examination of samples and compared with the assumed penetration depth. The obtained results make it possible to evaluate the suitability of the proposed methodology for determining the cooling rate in the heat affected zone.